Who, why, where: an overview of determinants of sunbed use in Europe. (27th February 2019) - Suppa, M.; Gandini, S.; Bulliard, J.L.; Daxhelet, M.; Zamagni, M.; Forsea, A.M.; Longo, M.I.; del Marmol, V.
Abstract: Although exposure to indoor tanning has been established as a clear risk factor for skin cancer, sunbeds are still commonly used in Europe. Understanding the determinants of sunbed use in Europe is key to plan educational interventions, behavioural strategies and legislative measures, which should be tailored to subgroups with different risk profiles. Evidences show that the typical sunbed users in Europe are young‐adult women, with intermediate skin type, a current employment and a medium/high socio‐economic status. Typical users display sun‐seeking behaviours and other risky behaviours such as smoking. Indoor tanning seems more common in northern than southern Europe. However, sunbed use remains common in fair‐skinned individuals and among adolescents/pre‐adolescents. Commonly reported reasons for sunbed use in Europe include aesthetic motives (i.e. looking attractive), the pursue of a prevacation tan, the influence of peers/parents engaging in the same habit, and the treatment of health conditions. The most commonly reported places to get an artificial tan in Europe are tanning studios and beauty salons. However, sunbeds are also available in sport venues, such as swimming pools and gyms, hotels and private houses. All these factors should be taken into account when planning educational, behavioural and legislative interventions to reduce the popularity of artificial tanning in Europe.